Use of Audiovisual Media to Improve Learning Outcomes in Writing Fable Stories for Class X Students of SMKN 1 Sengkang (Tamaddun, 2022)
This research is a class action research that aims to find out how the application of Audiovisual Media in Improving Learning Outcomes of Class X Students of SMK Negeri 1 Sengkang.  This type of research is class action research (PTK). The research consists of three stages, namely precyclical, cycle I, and cycle II. Data collection techniques are carried out by tests and nontests. Test techniques are in the form of written tests of writing fables, while non-test techniques include observation techniques, questionnaires, interviews, field notes, and documentation. The instruments used in this study were test and non-test instruments. In data analysis, qualitative and quantitative techniques are used. The aspects observed are changes in student attitudes during the learning process using audiovisual media carried out quite well and changes in student attitudes and student learning outcomes have improved.  This can be seen from the percentage of learning outcomes in the precyclical stage of only 58.00%. After applying audiovisual media, student learning outcomes increased to 70.56% in cycle I and increased again to 86.75% in cycle II.  Thus, it can be concluded that there is an increase in learning outcomes in writing fable stories by applying the concept of audiovisual media to class X students of SMK Negeri 1 Sengkang.